Edukasi Pengelolaan Keuangan Rumah Tangga Bagi Generasi X dengan Metode Kakeibo - Anisa Kusumawardani; Dhian Andanarini Minar Savitri; Rahmania Mustahidda; Maulana Ihsan Yusufi S; Ida Ayu (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The inability of a married couple to manage income, especially if the income earned is mediocre, will be disastrous for the integrity of the household. Expenses should be managed as well as possible according to the size of the income received. Generation X is a hardworking generation that does not really follow the existing technology, therefore it is difficult to provide counseling on financial literacy when following the times, namely by utilizing smartphone technology. Kakeibo is a Japanese method of saving money that is widely practiced by housewives in Japan. This method means 'household financial ledger'. In Indonesia and most countries, women still play an important role in household fincdferdfances. According to a survey conducted by the Financial Services Authority (OJK), planning and decision-making in the family are dominated by women. So, the partners in this program are PKK RT 05 RW 06 women in Plamongan Sari Semarang village as one of the solutions to reduce the divorce rate due to economic factors. The solution in this community service is training in household financial planning and training in making simple financial records. Planning and making simple financial records are carried out by applying the kakeibo method because the financial planning method originating from Sakura country is easily understood by mothers who are not proficient in using smartphones and other digital tools.